Percutaneous management of coronary artery fistula in acute coronary syndrome using a covered stent crush technique: a case report - Vedat Aslan; Sefa Sural (BMC Cardiovascular Disorders)
Abstract Background Coronary artery fistulas (CAFs) are abnormal vascular connections that allow blood to drain from another vessel or heart chamber, potentially leading to angina and heart failure. While often discovered incidentally, medium-sized and large CAFs necessitate closure to prevent hemodynamic complications. This case report describes a novel application of the bifurcation ‘crush’ technique in the treatment of a coronary artery fistula. Case presentation A 72-year-old woman was admitted to the emergency department with chest pain and was diagnosed with non-ST elevation myocardial infarction (MI). Coronary angiography revealed severe coronary stenosis and a large fistula. The large fistula was successfully treated by crushing a covered stent. This method treats the coronary fistula as a side branch while identifying the originating vessel as the main vessel. A covered stent is inserted into the coronary fistula, extending to the main vessel. The protruding segment is subsequently crushed via an open-cell drug-eluting stent parked within the main vessel. Conclusion This case highlights a different technique for managing large coronary fistulas among nonsurgical options. The use of drug-eluting stents to crush a covered stent effectively manages coronary fistulas, offering an alternative to traditional surgical or percutaneous methods. However, the absence of follow-up imaging limits the ability to confirm long-term stent patency or detect restenosis.